The Eastern Caribbean Economic and Currency Union : Macroeconomics and Financial Systems - Schipke, Alfred; Cebotari, Aliona; Thacker, Nita. (Washington, D.C. : International Monetary Fund, 2013)
The Eastern Caribbean Economic and Currency Union (OECS/ECCU) is one of four currency unions in the world. As in other parts of the world in the aftermath of the global economic and financial crisis, the region is at a crossroads, facing the major challenges of creating jobs, making growth more inclusive, reforming the banking system, and managing volatility, while grappling with high public debt and persistent low economic growth. Policymakers have the critical task of implementing strong reforms to strengthen the monetary union while also laying the foundation for accelerating growth. This Handbook provides a comprehensive analysis of the key issues in the OECS/ECCU, including its organization and economic and financial sector linkages, and provides policy recommendations to foster economic growth.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet